Consumer Protection Against the Production and Sale of Syrup Drugs Suspected of Being Contaminated with Hazardous Materials - Nomensen Freddy Siahaan (Journal of Social Research, 2023)
Recently, the Indonesian health world has been shocked by the alleged production and sale of syrup drugs suspected to be contaminated with Ethylene Glycol (EG)/Diethylene Glycol (DEG) which exceeds the safe threshold and triggers acute renal failure in children. This is very worrying because it is feared that the impact will be even wider. Based on the information cited by the author from the news article that the Food and Drug Supervisory Agency of the Republic of Indonesia (BPOM RI) released an updated list of ethylene glycol (EG)/Diethylene Glycol (DEG) tainted syrup drugs that exceed the safe threshold. The contamination is suspected of triggering acute renal failure in children. The method which was used in this Scholar Paper was the Qualitative Research Method, a kind of Normative Legal Writing which was based on prescriptive library research concerning the study of positive law. For the Primary Legal Materials, Scholar used references such as Act Number 8 Year 1999 regarding to Consumer Protection, etc. And for Secondary Legal Material, Scholar uses books, journals, papers, newspapers, and report of legal writing. Then, for Tertiary Legal Materials, Scholar used references such as legal dictionary, dictionary Indonesian-English dictionary and vice versa, etc. Consumer has rights that must be protected from legal perspectives. Law Number 8 of 1999 concerning Consumer Protection Article 1 point (2) states that consumers are every user of goods and or services available in society, whether for the benefit of themselves, family, others, or other living beings and not for trading. It is crystal clear as regulated by our legislation, Consumer Protection must have a guarantee of legal certainty given to consumers. In this case Consumer Protection must have a guarantee of legal certainty provided to consumers in this case is a guarantee of the safety of syrup drugs on the market so that they are safe for consumption by their buyers. Plus buyers who take the syrup medicine are in an unwell state. Of course they want what is called healing, instead of getting worse, conditions such as kidney failure or even death.